PENGARUH GREEN WORK–LIFE BALANCE, ORGANISATIONAL CULTURE, DAN GREEN INNOVATION TERHADAP EMPLOYEE RETENTION PADA SEKTOR BISNIS BERKELANJUTAN - Dhiyaa Raihan; Tiara Puspa (EBID: Ekonomi Bisnis Digital, 2026)
The development of sustainable business encourages companies not only to focus on profit, but also to pay attention to social, environmental, and employee welfare aspects. In this context, a company’s ability to retain employees or employee retention becomes an important factor in maintaining organizational stability and sustainability. This study aims to analyze the influence of Green Work–Life Balance, Organisational Culture, and Green Innovation on Employee Retention in sustainable business sector companies. This study used a quantitative approach with a survey method through questionnaire distribution to Shopee Indonesia employees selected using purposive sampling technique. The data were analyzed using SPSS and AMOS through validity test, reliability test, goodness of fit, and hypothesis testing using Structural Equation Modeling (SEM). The results showed that Green Work–Life Balance had a positive and significant effect on Employee Retention with a significance value of 0.005 < 0.05. Organisational Culture also had a positive and significant effect on Employee Retention with a significance value of 0.000 < 0.05. Meanwhile, Green Innovation showed a positive but insignificant effect on Employee Retention with a significance value of 0.187 > 0.05. These findings indicate that sustainability-based work–life balance and positive organizational culture have an important role in increasing employee loyalty and willingness to remain in the company. This study is expected to contribute to the development of sustainable human resource management literature and become a reference for companies in designing sustainability-based employee retention strategies.